ANALISIS NOVEL 5 CM KARYA DONNY DHIRGANTORO DENGAN PENDEKATAN SEMIOTIK - Kartini Kartini; Sarwit Sarwono; Bustanuddin Lubis (Universitas Bengkulu, 2017)
This research goals for understand figure and meaning the get in interior novel 5 cm by Donny Dhirgantoro. The method use interior research this is method qualitative. The approachment do interior in research is approachment semiotic. The Product obtained interior this research is figure and the meaning do this interior novel 5 cm by Donny Dhirgantoro the category to interior three species sign. Firts, icon, five meaning five people the already be friend since long, alway do together, and not possess friend other. Four man meaning four people man the ride carriage not buy the ticket. Second, index that is one purpose meaning togetherness, caused by already be friend since long. Third, symbol, is three minutes meaning agreement reached the in made by for sahabat (except Ian) if perforce say that ugliness or vice other people. 5 cm meaning people five friend the not never give up for the ideals of. The research can conclusion that figure and meaning that get in novel 5 cm karya Donny Dhirgantoro is: icon, that is five, one bowl, one people two sheet, three-three, one people, two hand, two great creature, four man, three kind, and three month. Index, that is one goals. Symbol, that is three minutes, one same other, direction at nine o’clock, direction at six o’clock, two worl, six the point of small, a thousand face, 5 centimeter, a thousand times, the kind third, and there’s one.